2013
DOI: 10.1371/journal.pone.0053196
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection for Quantitative Real-time PCR Normalization in Caragana intermedia under Different Abiotic Stress Conditions

Abstract: Quantitative real-time reverse transcription polymerase chain reaction (qPCR), a sensitive technique for gene expression analysis, depends on the stability of the reference genes used for data normalization. Caragana intermedia, a native desert shrub with strong drought-resistance, sand-fixing capacity and high forage value that is widespread in the desert land of west and northwest China, has not been investigated regarding the identification of reference genes suitable for the normalization of qPCR data. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 44 publications
12
153
0
1
Order By: Relevance
“…It should be noted that Rer1 and ATPase genes that were included as candidates on the basis of their stability of expression in a differential macroarray hybridization of alfalfa ESTs had not been previously tested as putative reference genes in other species. New reference genes identified by microarray analysis in Arabidopsis thaliana [33] and soybean (Glycine max) [34] were shown to outperform commonly used housekeeping genes in these species and other plant systems as well [21]. It is also noteworthy that eEF-1α consistently maintained an M value well below the 0.5 geNorm threshold across all treatments and genetic sources and is another candidate to consider in the validation of reference genes in RT-qPCR analysis of gene expression in alfalfa.…”
Section: Stability Of the Expression Of Candidate Reference Genesmentioning
confidence: 90%
See 2 more Smart Citations
“…It should be noted that Rer1 and ATPase genes that were included as candidates on the basis of their stability of expression in a differential macroarray hybridization of alfalfa ESTs had not been previously tested as putative reference genes in other species. New reference genes identified by microarray analysis in Arabidopsis thaliana [33] and soybean (Glycine max) [34] were shown to outperform commonly used housekeeping genes in these species and other plant systems as well [21]. It is also noteworthy that eEF-1α consistently maintained an M value well below the 0.5 geNorm threshold across all treatments and genetic sources and is another candidate to consider in the validation of reference genes in RT-qPCR analysis of gene expression in alfalfa.…”
Section: Stability Of the Expression Of Candidate Reference Genesmentioning
confidence: 90%
“…This is in stark contrast with the highly stable expression of UBL-2a and 18S-rRNA under these experimental conditions. Act has been previously shown to be unstable under various experimental conditions and was deemed unsuitable to normalize stress-induced gene expression in several species [12] [21] [32] including alfalfa [30]. Rapacz et al [18] concluded that the stability of Act in barley (Hordeum vulgare) exposed to abiotic stress could depend on the developmental stage.…”
Section: Stability Of the Expression Of Candidate Reference Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 of these 13 genes are similar to genes that in other plant species have been reported to be upregulated under abiotic stresses. These are the isoflavone reductase-like protein in grapefruit induced in response to UV irradiation, in coffee during a stress-response in leaves, and in rice induced by gibberellic acid (Lers et al, 1998;Brandalise et al, 2009;Wen et al, 2010); vacuolar processing enzyme in radish involved in floral bud abortion under heat stress, and in Malus hupehensis and Arabidopsis in response to high temperature stress (Zhang et al, 2013;Su et al, 2015); cytochrome P450 induced by salt and mannitol treatments in apple . Further, the sulphate transporter gene, which can be induced by both sulphur starvation and mycorrhiza formation in Lotus (Giovannetti et al, 2014).…”
Section: Identification Of I Argentea Genes With An Enhanced Expressmentioning
confidence: 99%
“…Reactions were performed in triplicate. Relative expression values were normalized to IaPTB, IaSAND, and IaUNK1 reference genes (Kakar et al, 2008;Zhu, 2013), which are stable expressed in different organs (Fig. S1).…”
Section: Real Time Quantitative Pcr Expression Analysismentioning
confidence: 99%